PEMBERDAYAAN ZAKAT PADA MASYARAKAT MODERN (Solusi Untuk Mengurangi Kemiskinan di Masyarakat) - - Julianto; - Fachrurrazi; Syamratun Nurjannah (Jurnal Imagine, 2023)
This study discusses "Zakat Empowerment in Modern Society (Solutions to Reduce Poverty in Society)". Furthermore, the main focus is limited to a sub-focus, namely: how is the right form of zakat management to attract public interest in paying zakat, how is the form of zakat empowerment in zakat institutions as an effort to alleviate poverty. This type of research uses a qualitative descriptive method, which is meant by descriptive research, namely investigating circumstances, conditions or others. The primary data obtained in this study was from LAZISMU West Kalimantan, then secondary data was obtained from books, journals, articles related to research. The results of this study are that 1. in the management of zakat there are several principles that must be followed and adhered to so that management can succeed as expected, including: the principle of openness, the principle of voluntary, the principle of integration, the principle of professionalism, the principle of independence. 2. The existence of productive activities, where the source of capital comes from zakat funds, is expected to make zakat funds more useful, especially to improve the standard of living of the middle and lower class people. Zakat assets can be developed, utilized or managed and developed in such a way with a form of working capital that is tailored to their expertise, so that it can bring benefits or results to people who are unable to improve their quality of life (especially the poor) in the long term, with the hope that gradually one day he is no longer included in the mustahik zakat group but can also become a muzakki (a person who gives zakat funds).